Domain Adaptation for Roasted Coffee Bean Quality Inspection - Cheng-Lung Chang; Shou-Chuan Lai; Ching-Yi Chen (International Journal of Engineering and Technology Innovation, 2024)
Current research in machine learning primarily focuses on raw coffee bean quality, hampered by limited labeled datasets for roasted beans. This study proposes a domain adaptation approach to transfer knowledge acquired from raw coffee beans to the task of inspecting roasted beans. The method maps the source and target data, originating from different distributions, into a shared feature space while minimizing distribution discrepancies with domain adversarial training. Experimental results demonstrate that the proposed approach effectively uses annotated raw bean datasets to achieve a high-performance quality inspection system tailored specifically to roasted coffee beans.